The Effect of Career Development, Salary and Workload Satisfaction on Turnover Intention in Generation Z - Risma Agistya Rahmawati; Nessa Atfella (DPPM Universitas Pelita Bangsa, 2024)
Moving intentions among Generation Z employees have become an increasing concern for organizations, given their unique work expectations and preferences. This study investigates the impact of career development opportunities, salary satisfaction, and workload satisfaction on the intention to move within this demographic group. Using quantitative research methods, data was collected through surveys distributed to Generation Z employees in various industries. These findings reveal that limited career development opportunities significantly encourage the intention to move, as Generation Z highly values growth and learning. Dissatisfaction with salary also emerged as a key factor influencing their desire to leave, underscoring the importance of fair and competitive compensation. In addition, dissatisfaction with workload, especially the perception of unfair or excessive workload, contributes to increased intention to move. These results highlight the need for organizations to devise specific strategies that address career development, salary structures, and workload management to effectively retain Generation Z employees and foster organizational loyalty over the long term.